Does cycling affect motor coordination of the lower limbs during running to exhaustion in well-trained triathletes? - Bieuzen, F.; Le Meur, Y.; Dorel, S.; Brisswalter, J.; Hausswirth, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Triathletes report incoordination when running after cycling. In recent study, Chapman et al. [1] have tried to measure this on one muscle: the tibialis anterior (TA). They showed that TA recruitment does not change during cycling to running transition. However, running and cycling imply the coordination of many muscles, and lots of works showed that fatigue affect not only the TA but also the other muscles of the lower limb. Within this framework, the aim of this study was to analyse the effect of cycling on the locomotor pattern during running to exhaustion from measurements of the electromyographic surface activity of nine muscles of the lower limb. METHODS - We compared surface electromyographic (EMG) recording from nine muscles of the lower limb (biceps femoris (BF), semi-tendinosus (SM), vastus lateralis (VL), the rectus femoris (RF), the vastus medialis (VM), the gastrocnemius lateralis (GL), the gastrocnemius medialis (GM), soleus (SOL) and tibialis anterior (TA)) during running to exhaustion (Tlim) immediately after 30min of cycling with a control-run (CR) test (no prior exercise). For each running test realised on a treadmill, intensity corresponding to the one measured at the second ventilatory threshold during a previous incremental running test. Three periods were compared: 75% of the five minute of the CR, 5% and 95% of the total time of the Tlim. RESULTS - The magnitude of the mean EMG RMS over the complete stride for the SM decrease significantly (p<0.05) between CR and the 5% and 95% of the Tlim. The mean EMG RMS for the GM decrease significantly (p<0.05) from 5% to 95% of the Tlim. The k values resulted from the cross-correlation technique [2] indicated that the activity of all muscles measured were not shifted in the stride but variability in muscle recruitment between athletes is great. CONCLUSION - Our results suggest that cycling does not influence running pattern of the main muscles of the lower limbs for well-trained population. However, using a treadmill modifies the EMG pattern of leg muscles [3] and could explain that. Moreover, contrary to previous studies, the leg muscle activity during running is not influenced neither by cycling nor fatigue except for SM and GM muscles. These results suggested that for training athlete locomotor pattern does not change over short period of running on treadmill even if it was conducted until exhaustion. BIBLIOGRAPHY 1 Chapman AR, Vicenzino B, Blanch P, Dowlan S, Hodges PW. Does cycling effect motor coordination of the leg during running in elite triathletes? J Sci Med Sport. 2008. 11(4):371-80. 2 Dorel S, Drouet JM, Couturier A, Champoux Y, Hug F. Changes of pedalling technique and muscle coordination during an exhaustive exercise. Med Sc Sports Exerc. 2009. In Press 3 Wank V, Frick U, Schmidtbleicher D. Kinematics and Electromyography of lower limb muscles in overground and treadmill running. Int J Sports Med. 1998. 19: 455-461.